The kynurenine pathway in HIV, frailty and inflammaging - Sultana, Shabiha; Elengickal, Anthony; Bensreti, Husam; de Chantemèle, Eric Belin; McGee-Lawrence, Meghan E.; Hamrick, Mark W. (Frontiers in Immunology, 2023)
Kynurenine (Kyn) is a circulating tryptophan (Trp) catabolite generated by enzymes including IDO1 that are induced by inflammatory cytokines such as interferon-gamma. Kyn levels in circulation increase with age and Kyn is implicated in several age-related disorders including neurodegeneration, osteoporosis, and sarcopenia. Importantly, Kyn increases with progressive disease in HIV patients, and antiretroviral therapy does not normalize IDO1 activity in these subjects. Kyn is now recognized as an endogenous agonist of the aryl hydrocarbon receptor, and AhR activation itself has been found to induce muscle atrophy, increase the activity of bone-resorbing osteoclasts, decrease matrix formation by osteoblasts, and lead to senescence of bone marrow stem cells. Several IDO1 and AhR inhibitors are now in clinical trials as potential cancer therapies. We propose that some of these drugs may be repurposed to improve musculoskeletal health in older adults living with HIV.